Teachers' screen-based repair practices in video-mediated Turkish as a foreign language classroom interactions - Karaca-Turhan, Fatma; Balaman, Ufuk; Bas, Bayram (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
The use of a shared screen plays a central role in the overall architecture of video-mediated interactions, and it becomes even more prominent when a teacher uses it for pedagogical purposes in online classes. In this study, we investigate an underexplored setting, fully-online, synchronous, video-mediated Turkish as a foreign language classrooms. Using multimodal conversation analysis to examine a dataset of screen-recorded video-mediated L2 classroom interactions consisting of a teacher and a small group of students with turned-off cameras, we focus on a recurrent interactional practice, namely screen-based repair, and outline the methods used by the teacher based on a collection of cases. The findings show that upon the identification of a trouble, whether the trouble source is visible on the screen or not, the teacher initiates, enacts and completes other-initiated other-repair by systematically drawing on diverse screen-based resources, and engages in writing aloud, highlighting aloud, and cursor marking aloud, in doing so, thus deploying the practice of screen-based repair to resolve technical, pedagogical, and interactional troubles. We argue that the findings not only describe the pedagogical context of a less taught language but also bring new insights into video-mediated L2 classroom interaction and online language teaching overall.
Keywords: Screen-based repair; video-mediated interaction; conversation analysis; online language teaching; Turkish as a foreign language; L2 INTERACTION; ENVIRONMENTS; ORGANIZATION; CHATS; TALK; Education & Educational Research; Linguistics